2018
DOI: 10.1115/1.4040019
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Impact Performance of Bicycle Helmets During Oblique Impacts

Abstract: Cycling is a leading cause of sport-related head injuries in the U.S. Although bicycle helmets must comply with standards limiting head acceleration in severe impacts, helmets are not evaluated under more common, concussive-level impacts, and limited data are available indicating which helmets offer superior protection. Further, standards evaluate normal impacts, while real-world cyclist head impacts are oblique-involving normal and tangential velocities. The objective of this study was to investigate differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 42 publications
1
53
0
Order By: Relevance
“…2,14 A previous oblique impact study using the HIII neck required greater normal velocities to produce the same PLAs as the present study. 1 It should thus be noted that the present kinematics and risks may be larger compared to tests with a neck. As advanced ATD necks are developed with improved biofidelity in axial compression, their effects in oblique impacts should be investigated.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…2,14 A previous oblique impact study using the HIII neck required greater normal velocities to produce the same PLAs as the present study. 1 It should thus be noted that the present kinematics and risks may be larger compared to tests with a neck. As advanced ATD necks are developed with improved biofidelity in axial compression, their effects in oblique impacts should be investigated.…”
Section: Discussionmentioning
confidence: 90%
“…40 Conversely, an additional study demonstrated higher PRA for MIPS helmets compared to non-MIPS helmets. 1 The latter study incorporated a HIII neck, which likely influenced results. Further, only two MIPS helmets were included, and both produced greater PLAs, suggesting that additional design factors led to reduced impact protection overall.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations